RNA-Based Therapeutics in Genetic Neurodevelopmental Disorders: Bridging Molecular Genetics and Precision Medicine - Ina-Ofelia Focșa; Catrinel Iliescu; Cristina Pomeran; Magdalena Budișteanu; Carmen Sandu; Alice Denisa Dică; Florentina Ionela Lincă; Cristina Moțoiescu; Diana Bârcă; Ioana Minciu; Dana Craiu; Viorica Elena Rădoi (International Journal of Molecular Sciences, 2026)
Genetic neurodevelopmental disorders (NDDs) encompass a heterogeneous group of conditions characterized by impaired cognitive, behavioral, and neurological development resulting from pathogenic variants affecting brain development and synaptic function. Advances in molecular genetics and next-generation sequencing have significantly expanded the understanding of the genetic architecture underlying disorders such as Rett syndrome (RTT), Fragile X syndrome (FXS), Angelman syndrome (AS), and autism spectrum disorders. Beyond these classical neurodevelopmental disorders, spinal muscular atrophy (SMA) is included as a paradigmatic example of successful RNA-based therapeutic translation. Concurrently, RNA-based therapeutics have emerged as promising precision medicine strategies capable of modulating gene expression at the transcriptional and post-transcriptional levels. These approaches include antisense oligonucleotides (ASOs), small interfering RNAs (siRNAs), messenger RNA (mRNA) therapies, RNA editing technologies, and splice-modulating agents. Recent clinical successes, particularly in spinal muscular atrophy, have demonstrated the transformative potential of RNA therapeutics in neurological disease. However, substantial challenges remain, including BBB penetration, long-term safety, immune activation, and genotype-specific variability in therapeutic response. This review summarizes current advances in RNA-based therapeutics for genetic NDDs, highlighting molecular mechanisms, disease-specific therapeutic strategies, translational progress, delivery challenges, and future directions. Overall, continued progress will depend on the integration of disease biology, rational RNA therapeutic design, and effective CNS-targeted delivery, supporting the broader implementation of precision RNA medicine for genetic neurodevelopmental disorders.